New Development Encounters: China and Brazil in African Agriculture. (28th June 2013) - Scoones, Ian; Cabral, Lídia; Tugendhat, Henry
Abstract There is currently much talk of the role of the 'rising powers' in Africa, and whether their engagements represent a 'new paradigm' in development cooperation. This article introduces this IDS Bulletin and examines Brazilian and Chinese agricultural development cooperation in Ethiopia, Ghana, Mozambique and Zimbabwe. A wide variety of forms of support are seen, involving different financial modalities, including aid, concessional loans, trade deals and commercial investment. Our focus is on the 'encounters' that occur during negotiations and the intersection of wider framing discourses with practices on the ground in particular projects. Brazilian and Chinese domestic political dynamics, competing social imaginaries and histories of agrarian change all shape development cooperation. Meanwhile, African governments are not just passive recipients; they exert agency in negotiations, trading off different players. Outcomes depend on the particular context, and the new aid and investment scene in African agriculture is highly varied, presenting opportunities as well as challenges for the future.